حلال و حرام کے متعلق شرعی معیارات: Shari'ah standards regarding halal and haram - Ahmed , Gul (Journal of Quranic and Social Studies, 2021)
The religion of Islam is a complete system of life, For Muslims, halal food has a fundamental religious significance, Muslims in any corner of the world use halal food, From the word food, the focus is on food and drink But this is a limited concept ,Nowadays, the term halal food is used in a broad context Halal food refers not only to chicken and beef but also to halal food services and beverages cosmetics, perfumes, even rice, water, poultry food ,leather and textile products. In the preparation of which the Islamic point of view is given special importance and care is taken that no haraam element is included in it. Islam also gives us complete guidance regarding halal food because in the light of Shari'ah, the food that is obtained will be considered halal. The religion of Islam encourages its followers to eat halal food, because halal food has a profound effect on human nature. Where we are encouraged to eat halal food, we are also encouraged to avoid haraam food, Analyzing these injunctions of Islam regarding individual and collective life, they can be summarized in two words, halal and haraam.